Preceptor's Anxiety In Performing Supervision and Supervision of Nursing Students in Practices During the Covid-19 Pandemic - Yuniar Mansye Soeli; Rachmawaty Dirham Hunawa; Dewi Modjo (Jurnal Keperawatan, 2022)
The Covid-19 pandemic has become a top priority for crisis health especially around the world. The Covid-19 pandemic has changed the way the public works, learns, meets every day needs until interacts. Restrictions and Lockdown policy can increase level worry someone. Anxiety is feeling nervous or restless. People tend experience it moment be in a situation certain, wrong the only one when a mentor academic must guide and supervision college student his by directly on the ground practice. This present study aimed to explore the preceptor's anxiety in performing guidance and supervision of nursing students in practices during the covid-19 pandemic. This quantitative research relied on a descriptive method with a descriptive survey approach towards 30 respondents that is whole preceptor or lecturer mentor academic college nursing students. The sample was selected by employing the purposive sampling technique. The data collection instrument used in this study was a questionnaire through Google forms. The results of the study based on age characteristics were 27 respondents (91%) of which aged 26-35 years, 2 respondents (6%) aged 46-55 years, and 1 respondents (3%) aged 56-65 years. Based on gender characteristics dominated by women as many as 21 respondents (70%). The results of the study on the level of anxiety were 28 respondents (88%) were in the low level of anxiety, while 2 respondents (12%) were in the category of moderate anxiety level. It is hoped that the preceptor must be able to control feelings of worry and anxiety so that it does not become an anxiety disorder. Besides that preceptors must have activity guidelines that are in accordance with health protocols according to applicable regulations so that they can reduce anxiety during the Covid-19 pandemic.